Comparison of postoperative skeletal stability of maxillary segments after Le Fort I osteotomy, using patient-specific implant versus mini-plate fixation. Issue 7 (July 2019) - Kotaniemi, Karoliina V.M.; Heliövaara, Arja; Kotaniemi, Miika; Stoor, Patricia; Leikola, Junnu; Palotie, Tuula; Suojanen, Juho
Abstract: Background: Three-dimensionally (3D) designed osteotomies and customised osteosynthesis are rapidly becoming standard in maxillofacial reconstructive and deformity surgery. Patient-specific implants (PSIs) have been in use for a few years in orthognathic surgery as well. In Le Fort I osteotomy, wafer-free fixation of the maxillary segment can be performed by individually manufactured cutting and drill guides together with PSIs. Aim: This retrospective study was performed to compare the postoperative skeletal stability of the maxillary segment fixed by patient-specific implants versus mini-plates after Le Fort I osteotomy. Patients: Fifty-one patients were divided into subgroups according to the fixation method and the advancement of the sub-spinal point. The postoperative skeletal stability of the maxillary segment was evaluated from lateral cephalometric radiographs one year postoperatively. Results: No statistically significant differences were found between the postoperative skeletal stability of the PSI and mini-plate fixed maxillae. Prospective studies, possibly with 3D fusion analysis, are warranted to confirm the results. Conclusion: The choice between the two fixation methods does not seem to affect the postoperative skeletal stability of the maxillary segments.